2013
DOI: 10.1128/aem.02696-13
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Mechanism of Biocatalyst Inhibition in Microbial Desulfurization

Abstract: Microbial desulfurization, or biodesulfurization (BDS), of fuels is a promising technology because it can desulfurize compounds that are recalcitrant to the current standard technology in the oil industry. One of the obstacles to the commercialization of BDS is the reduction in biocatalyst activity concomitant with the accumulation of the end product, 2-hydroxybiphenyl (HBP), during the process. BDS experiments were performed by incubating Rhodococcus erythropolis IGTS8 resting-cell suspensions with hexadecane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
70
2

Year Published

2016
2016
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 70 publications
(80 citation statements)
references
References 22 publications
8
70
2
Order By: Relevance
“…As shown in figure 4A, a high initial removal rate of DBT was observed, but the reaction slowed down after 15 min and 30% of the substrate (DBT) remained in the medium at the end of the resting cell process. These results, therefore, confirmed in vivo the inhibitory effects of HBPS on the DszC activity observed in vitro (Abin-Fuentes et al, 2013).The dszA1-D1 cassette (Fig. 1C) completely converted DBTO 2 into HBPS in about 120 min (Fig.…”
supporting
confidence: 74%
See 4 more Smart Citations
“…As shown in figure 4A, a high initial removal rate of DBT was observed, but the reaction slowed down after 15 min and 30% of the substrate (DBT) remained in the medium at the end of the resting cell process. These results, therefore, confirmed in vivo the inhibitory effects of HBPS on the DszC activity observed in vitro (Abin-Fuentes et al, 2013).The dszA1-D1 cassette (Fig. 1C) completely converted DBTO 2 into HBPS in about 120 min (Fig.…”
supporting
confidence: 74%
“…Moreover, decay of the BDS activity due to the accumulation of the sulfur-free end product 2HBP in bacterial biocatalysts has been reported (Abin-Fuentes et al, 2013). It has been shown that bacteria harboring identical dsz genes provide different BDS rates due to the influence of the host metabolism (Kilbane, 2006 (Kilbane, 2006;Li et al, 2008;Ma et al, 2006;Shavandi et al, 2009; Wang et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations